Pengaruh Etika Pelayanan Publik Terhadap Kepuasan Masyarakat di Kantor Desa Tonronge Kabupaten Sidenreng Rappang - Darmawati, Darmawati; Astinah Adnan, Andi; Mannu, Ahmad; Lukman, Lukman (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study aims to determine the effect of public service ethics on community satisfaction at the Tonronge Village Office, Baranti District, Sidenreng Rappang Regency. The explicit purpose of the research is to analyze the extent to which public service ethics affect community satisfaction with services at the village level. The method used was quantitative and associative, with 68 people who received services for two months using a saturated sampling technique. Research variables include public service ethics (X) and community satisfaction (Y). Data were collected through observation, questionnaires, and literature studies, then analyzed using IBM SPSS Statistics 21.0. The results showed that public service ethics significantly affected community satisfaction, with satisfaction levels of 65.5% and 68.8%, respectively. Factors that influence this relationship have a satisfaction level of 61%. The ANOVA test shows Fcount 125.312 with a significance of 0.000, while the t-test shows tcount (11.194) > stable (1.688), which means that public service ethics has a significant effect. The R square value of 66% indicates that public service ethics influences 66% of public satisfaction, while other factors outside this study influence 34%.